Natural Seepage of Methane and Light Alkanes at Three Locations in Southern California - Brynne M. Weed; Gisselle D. Brambila; Lambert A. Doezema (Atmosphere, 2020)
Methane and light (C2–C5) alkane fluxes were measured from three geologic seepage sites in Southern California during May and June of 2019. Samples were collected from visible macroseeps in Carpinteria, McKittrick, and Ojai using an aluminum flux chamber with attached stainless-steel canisters and were analyzed for C1 to C5 alkanes via gas chromatography. Carpinteria fluxes were characterized by a lower percentage of volatile organic compounds relative to methane but greatly enhanced (~20:1) ratios of i-butane to n-butane. McKittrick and Ojai exhibited less methane-rich emissions and i-butane to n-butane ratios of less than 2:1. The differences between gas ratios observed at the surface and those previously reported from underground gas deposits at Ojai suggest that gases undergo alterations to their molecular composition between deposit and surface. The ratios of emitted gases in this study show that not only does geologic seepage have a much different volatile organic compound profile than oil and natural gas extraction and pipeline natural gas, but also that individual geologic seepage locations exhibit large variability.